Comparative genome analysis of Clostridium beijerinckii strains isolated from pit mud of Chinese strong flavor baijiu ecosystem. Issue 11 (6th September 2021) - Zou, Wei; Ye, Guangbin; Liu, Chaojie; Zhang, Kaizheng; Li, Hehe; Yang, Jiangang
Abstract: Clostridium beijerinckii is a well-known anaerobic solventogenic bacterium which inhabits a wide range of different niches. Previously, we isolated five butyrate-producing C. beijerinckii strains from pit mud (PM) of strong-flavor baijiu (SFB) ecosystems. Genome annotation of the five strains showed that they could assimilate various carbon sources as well as ammonium to produce acetate, butyrate, lactate, hydrogen, and esters but did not produce the undesirable flavors isopropanol and acetone, making them useful for further exploration in SFB production. Our analysis of the genomes of an additional 233 C. beijerinckii strains revealed an open pangenome based on current sampling and will likely change with additional genomes. The core genome, accessory genome, and strain-specific genes comprised 1567, 8851, and 2154 genes, respectively. A total of 298 genes were found only in the five C. beijerinckii strains from PM, among which only 77 genes were assigned to Clusters of Orthologous Genes categories. In addition, 15 transposase and 12 phage integrase families were found in all five C. beijerinckii strains from PM. Between 18 and 21 genome islands were predicted for the five C. beijerinckii genomes. The existence of a large number of mobile genetic elements indicated that the genomes of the five C. beijerinckii strains evolved with the loss or insertion of DNA fragments in the PM of SFB ecosystems. This study presents a genomic framework of C. beijerinckii strains from PM that could be used for genetic diversification studies and further exploration of these strains.